Pisarz zapomniany. Twórczość Zygmunta Krzyżanowskiego w kontekście czasopism literackich Związku Sowieckiego - Łaniewski, Paweł (Rusycystyczne Studia Literaturoznawcze, 2019)
The article presents the contacts of Sigizmund Krzhizhanovsky, a Russian writer of Polish origin, with literary magazines of the first decades of Soviet Russia. Krzhizhanovsky, as a representative of the avantgarde and the Polish nobleman, met with a politically motivated ban on printing. Most of his works were published for the first time only during the period of perestroika. Some of his smaller works, however, saw the light of day thanks to literary magazines. The aim of the article is to present the socio-political situation in which the writer found himself and to outline the balance of power prevailing in the literary life of the time.